Interdisciplinary Analysis of Textbooks of New Senior English for China - Liang, Junjie (Journal of Theory and Practice in Education and Innovation, 2024)
Interdisciplinarity or interdisciplinary studies involves the combining of two or more academic disciplines into one activity. As the carrier of interdisciplinary materials, the interdisciplinary characteristics of teaching materials can effectively promote the integration of subject knowledge and the implementation of interdisciplinary education on the premise of satisfying students’ interests and development. Through the content analysis method and quantitative analysis method, this paper conducts an interdisciplinary comparative analysis of readings of the required modules 1-5 of senior high school English textbooks of people’s education press from an interdisciplinary perspective. It is found that the textbooks of the people’s education press reflect the interdisciplinary nature in a balanced manner, and the proportion of humanities and social sciences is higher than that of other subjects. Given this study, the paper gives the possible reasons for selection of materials and themes, as well as the possible improvement directions and suggestions put forward by the author.